Pengaruh Kombinasi Ekstrak Batang Brotowali (Tinospora crispa L.) dan Daun Belimbing Wuluh (Averrhoa bilimbi L.) Terhadap Intensitas Serangan Serangga Hama pada Tanaman Bayam Cabut (Amaranthus tricolor L.) var. Maestro - Amelia Tya Nabila Amelia Tya Nabila; Sonja Verra Tinneke Lumowa; Zenia Lutfi Kurniawati; Suparno Putera Makkadafi (PendIPA Journal of Science Education, 2026)
Pest infestations are one of the limiting factors in the cultivation of pull-up spinach, which can reduce crop quality and productivity. Pest control methods that still rely heavily on chemical pesticides have the potential to disrupt the environmental balance. The development of botanical pesticides is an approach that continues to be studied as a more ecological method of pest control. The stems of brotowali and the leaves of belimbing wuluh are known to contain bioactive compounds that have the potential to be utilized as botanical pesticide ingredients. This study aims to determine the effect of a combination of extracts from brotowali stems (Tinospora crispa L.) and belimbing wuluh leaves (Averrhoa bilimbi L.) on the intensity of pest insect attacks on Maestro variety spinach (Amaranthus tricolor L.) plants, as well as to determine the optimal concentration of the combination. This study is an experimental study using a non-factorial Randomized Block Design (RBD) with five treatment levels, namely 0% (control), 15%, 30%, 45%, and 60%, with five replicates. The observed parameter was the intensity of insect pest attacks based on the level of leaf damage at 14, 19, 24, 29, dan 34 day after sowing. The data were analyzed using analysis of variance (ANOVA) and followed by the Least Significant Difference (LSD) test at a 1% significance level. The results of the study showed that the calculated F-value at all observation time was greather than the critical F-value at the 1% level, thus the combination of brotowali stem extract and belimbing wuluh leaf extract had a highly significant effect on the intensity of pest insect attacks on Maestro variety spinach. The 60% concentration proved be the most effective in suppressing the intensity of pest insect attacks.